2006
DOI: 10.1007/bf03022875
|View full text |Cite
|
Sign up to set email alerts
|

Documentation on the anesthetic record: correlation with clinically important variables

Abstract: McGill anesthesiologists consider many preoperative and intraoperative variables to be important to document on the anesthetic record. However, subsequent chart review indicated that many of these variables are recorded inconsistently. The transmission of anesthesia-related medical information might be improved if anesthesiologists recorded more consistently information they consider to be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…12 In addition, reporting a difficult airway is always a subjective issue, making it difficult to follow-up and prepare for a subsequent intubation, especially when a patient is then treated in another hospital and by another anaesthesiologist. 13 In some institutions, after operation, information is communicated to patients concerning their difficult airway management, either verbally or in written form. Half of these patients informed verbally forget their notification.…”
mentioning
confidence: 99%
“…12 In addition, reporting a difficult airway is always a subjective issue, making it difficult to follow-up and prepare for a subsequent intubation, especially when a patient is then treated in another hospital and by another anaesthesiologist. 13 In some institutions, after operation, information is communicated to patients concerning their difficult airway management, either verbally or in written form. Half of these patients informed verbally forget their notification.…”
mentioning
confidence: 99%
“…There were missing data for ASA physical status and emergency category. In the logistic regression model, only the cohort of subjects with complete data in all variables was considered . We used multiple imputations to assess the sensitivity of results to missing values .…”
Section: Methodsmentioning
confidence: 99%
“…Tessler surveyed the opinions of anesthesiologists to determine the variables they felt to be most important to document on the anesthetic record [35]. His subsequent chart review found that many of the variables considered important were infrequently recorded.…”
Section: Quality and Accuracy Of Contentmentioning
confidence: 99%